Implementation and effects of the “Family 500+” programme in Poland (Economic and Political Thought, 2020)
The article aims to analyse the impact of the government supportprogramme “Family 500+” on the socioeconomic situation in Poland.The programme has been operating since April 2016, and it consistsin the provision of monthly benefits to parents bringing up children. Thebenefit is granted for every child under the age of 18. The programme issupposed to reverse the drop in the number of births observed for manyyears as well as to improve the living conditions of the poorest families, and,in particular, to eliminate the phenomenon of extreme poverty. However,statistical data show that despite ambitious assumptions, the programmehas not contributed to the improvement of the demographic situation of thecountry and the financial situation of families.
Keywords: demography, pro-family policy, “Family 500+” programme, poverty